Explore Westonci.ca, the leading Q&A site where experts provide accurate and helpful answers to all your questions. Connect with a community of experts ready to help you find solutions to your questions quickly and accurately. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.

Use composition to determine if [tex]$G(x)[tex]$[/tex] or [tex]$[/tex]H(x)[tex]$[/tex] is the inverse of [tex]$[/tex]F(x)[tex]$[/tex] for the limited domain [tex]$[/tex]x \geq -1$[/tex].

[tex]\[
\begin{array}{l}
F(x) = \sqrt{x + 1} \\
G(x) = x^2 - 1 \\
H(x) = x^2 + 1
\end{array}
\][/tex]

A. [tex]$G(x)[tex]$[/tex] is the inverse of [tex]$[/tex]F(x)$[/tex].

B. [tex]$H(x)[tex]$[/tex] is the inverse of [tex]$[/tex]F(x)$[/tex].

C. Neither function is the inverse of [tex]$F(x)$[/tex].

D. Both functions are inverses of [tex]$F(x)$[/tex].


Sagot :

To determine if \( G(x) \) or \( H(x) \) is the inverse of \( F(x) \) for the limited domain \( x \geq -1 \), we need to evaluate the compositions \( F(G(x)) \) and \( F(H(x)) \) and check if either composition equals \( x \).

Given:
[tex]\[ F(x) = \sqrt{x + 1} \][/tex]
[tex]\[ G(x) = x^2 - 1 \][/tex]
[tex]\[ H(x) = x^2 + 1 \][/tex]

### Composition of \( F \) and \( G \):

Let us first compute \( F(G(x)) \):
[tex]\[ F(G(x)) = F(x^2 - 1) = \sqrt{(x^2 - 1) + 1} = \sqrt{x^2} \][/tex]

Since we are given the domain \( x \geq -1 \), \( x \) can be positive or zero. Therefore:
[tex]\[ \sqrt{x^2} = |x| \][/tex]

But to maintain \( F(x) \) as an inverse function, we need \( \sqrt{x^2} \) to simplify exactly to \( x \) for all \( x \geq -1 \). Since \( \sqrt{x^2} \) is \( |x| \), it does not always simplify to \( x \) without further restricting the domain.

### Composition of \( F \) and \( H \):

Now, let us compute \( F(H(x)) \):
[tex]\[ F(H(x)) = F(x^2 + 1) = \sqrt{(x^2 + 1) + 1} = \sqrt{x^2 + 2} \][/tex]

Examining \( \sqrt{x^2 + 2} \) for any \( x \geq -1 \), it does not simplify to \( x \).

### Evaluating the Results:

For \( F(G(x)) \):
[tex]\[ F(G(x)) = |x| \][/tex]
And for \( F(H(x)) \):
[tex]\[ F(H(x)) = \sqrt{x^2 + 2} \][/tex]

Neither composition results in \( x \). Thus, neither \( G(x) \) nor \( H(x) \) is an inverse of \( F(x) \).

Therefore, the correct answer is:

C. Neither function is the inverse of [tex]\( F(x) \)[/tex].